2019
DOI: 10.3389/fmicb.2019.00084
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Non-toxigenic Clostridioides difficile Strains Isolated From Patients in Mexico

Abstract: Clostridioides difficile is a Gram positive, sporulated, rod-shape, anaerobic pathogen responsible for nosocomial diarrhea and colitis, mainly in antibiotic treated patients. C. difficile produce two toxins responsible for disease, toxin A (TcdA) and toxin B (TcdB), although not all strains produce them. Non-toxigenic C. difficile (NTCD) strains are able to colonize the intestinal mucosa and are often isolated from asymptomatic individuals. NTCD are poorly studied, their evolutionary history has not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Our remaining soil isolate was ribotype 511 and has not been associated with animal, food or human sources. However, due to the ribotype's lack of toxin genes, it may be carried asymptomatically [118] or be associated with hospital-acquired diarrhoea [119]. WGS analysis suggested that RT511 was most closely related to strain C. difficile W0003a, previously observed in clinical isolates in Korea [103].…”
Section: Ribotypes Of C Difficilementioning
confidence: 90%
“…Our remaining soil isolate was ribotype 511 and has not been associated with animal, food or human sources. However, due to the ribotype's lack of toxin genes, it may be carried asymptomatically [118] or be associated with hospital-acquired diarrhoea [119]. WGS analysis suggested that RT511 was most closely related to strain C. difficile W0003a, previously observed in clinical isolates in Korea [103].…”
Section: Ribotypes Of C Difficilementioning
confidence: 90%
“…The persistence of NTCD may stem from specific factors, or selective advantages allowing the occupation of the ecological niche. Concerning the antimicrobial susceptibility patterns, a recent work reported a higher resistance to MTZ in NTCD compared to toxigenic strains [ 32 ]. We did not confirm this finding since no MTZ MIC was above 0.75 mg/L ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…MS001 has a much higher number of genes (4110) compared to the other strains (ranging from 3629 to 3892) ( Table S3 ), and uniquely lacks the toxins TcdA and TcdB. Indeed, non-toxigenic C. difficile strains have distinct phenotypes compared to toxigenic strains, as a consequence of the variability in their genome 49 . In general, there is no pattern between the C. difficile isolates from healthy and sick individuals in terms of their genotype.…”
Section: Resultsmentioning
confidence: 99%